Evaluation of cytokines, oxidative stress markers and brain-derived neurotrophic factor in patients with fibromyalgia – A controlled cross-sectional study. (August 2016) - Ranzolin, Aline; Duarte, Angela Luzia Branco Pinto; Bredemeier, Markus; da Costa Neto, Cláudio Antônio; Ascoli, Bruna Maria; Wollenhaupt-Aguiar, Bianca; Kapczinski, Flávio; Xavier, Ricardo Machado
Highlights: The IL-6, IL-8, TNF-α, TBARS, protein carbonyl and BDNF did not differ between FM patients and controls. The IL-10 levels were higher in FM patients (adjusted p = 0.041). Among FM patients, there was no correlation of depression and disease impact scores with any biomarker tested here. Abstract: Objectives: Previous studies measuring serum levels of biomarkers of inflammation/oxidative stress and neurotrophins levels in fibromyalgia (FM) have rendered inconsistent results. In the present study, our aim was to explore the levels of interleukins, oxidative stress markers and brain-derived neurotrophic factor (BDNF) in patients with FM in relation to depression and severity of disease. Methods: In a prospective controlled cross-sectional study, serum concentrations of IL-6, IL-8, IL-10, TNF-α, thiobarbituric acid reactive substances (TBARS), protein carbonyl and BDNF were measured in 69 FM patients and 61 healthy controls (all women). In the FM group, the Fibromyalgia Impact Questionnaire (FIQ), the Beck Depression Inventory (BDI) and the Hamilton Depression Rating Scale (HDRS) were applied. Mann Whitney's and Spearman correlation tests were used for statistical analysis. Results: The FM patients demonstrated a significant impact of the disease on quality of life (FIQ 70.2 ± 17.8) and most of them had depression at some level (82.6% and 87.0% as assessed by BDI and HDRS, respectively). Most biomarkers (IL-6, IL-8, TNF-α, TBARS and protein carbonyl) and BDNF did not differ significantly between patients and controls, but the IL-10 levels were higher in FM patients (adjusted p = 0.041). Among FM patients, there was no correlation of HDRS, FIQ, and BDI scores with any biomarker tested here. Conclusion: We observed no significant differences in biomarkers between FM patients and controls, except for higher levels of IL-10 (an anti-inflammatory cytokine) in patients. The levels of biomarkers were not correlated with parameters of disease and depression severity.